Answer:
slope = -1
Step-by-step explanation:
you <u>subtract the y-values</u> (-1-1=-2) then <u>subtract the x-values</u> (6-4=2) then divide the sum of the y-values by the sum of the x-values
which simplifies to a slope of -1
To get the inverse of a function interchange
the x's with the y'x and solve for y, as follows:
y=5x-7
Interchange to get:
x=5y-7
Solve for y to get:
y=(1/5)x+(7/5)
so I think it might be c
X-coordinate: -.50
Y-coordinate: -.55
We have a function,
![f(x)=x^2-1](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2-1)
and we are asked to find its inverse function.
An inverse function essentially gets you the original value that was dropped into a function.
For example,
If I put 5 into
I will get 24. Now If I take 24 and put it into the inverse function I have to get number 5 back.
The way to determine the inverse function swap the x and the
, then solve for
,
![x=f(x)^2-1](https://tex.z-dn.net/?f=x%3Df%28x%29%5E2-1)
![f(x)^2=x+1](https://tex.z-dn.net/?f=f%28x%29%5E2%3Dx%2B1)
![f(x)=\pm\sqrt{x+1}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cpm%5Csqrt%7Bx%2B1%7D)
Of course the notation demands that the obtained function be called,
![f^{-1}(x)=\pm\sqrt{x+1}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cpm%5Csqrt%7Bx%2B1%7D)
Hope this helps :)